The mediated festival: Live music as trigger of streaming and social media engagement. (August 2019) - Danielsen, Anne; Kjus, Yngvar
Live music events are increasingly saturated with and mediated via the online and mobile devices of the audience. This article explores patterns in this media use surrounding the Øya festival in Norway and focuses, in particular, on music streaming and social media activity. It presents statistical analysis of listening sessions via the streaming service Wimp and social interactions via the micro-blogging platform Twitter. The juxtaposition of these unique access points allows the analysis to explore the impact of physical live concerts on the digital music experience. It also enables a nuanced examination of how the festival audience responds to different artist segments, from international headliners to local acts. One key finding is that local artists that are positively evaluated via Twitter have the greatest boost in subsequent music streaming. The article argues that in-depth studies of the intersection of live and mediated music are essential to understanding the encounter between artists and audiences that is facilitated by contemporary live music events.